The Dichotomy Between Film Music and Concert Music: Demonstrated By the Careers of Aaron Copland and Bernard Herrmann - (:unkn) unknown (My University, 2017)
Aaron Copland and Bernard Herrmann both began working in the film industry in 1939. Both were born in the United States, unlike many prominent composers working in Hollywood during the golden age, and both composed film scores and concert works. Copland composed mostly concert pieces while Herrmann composed mostly film scores. They worked in both the art music and popular music realms, yet they had to continually defend the validity of film music. Although this situation was not uncommon to composers working in Hollywood, this thesis focuses on the careers of Copland and Herrmann to demonstrate the dichotomy between film music and concert music. By contextualizing the careers of Copland and Herrmann within the broader culture of the United States during the early to mid-twentieth century, we can begin to understand how film music fits within music history. To fully understand this, we must rethink the rigid barrier placed between art music and popular music and the barrier between absolute music and pragmatic music, by realizing that these barriers were solidified at the turn of the twentieth century and were more or less foreign to people in the centuries preceding. In doing so, we might be able to understand how film music and art music influence each other, which could then inform how popular and pragmatic music have interacted with art music throughout history.
Keywords: Aaron Copland; Bernard Herrmann; Film Studies; Music